Hybrid Li/Na Ion Batteries: Temperature-Induced Reactivity of Three-Layered Oxide (P3-Na2/3Ni1/3Mg1/6Mn1/2O2) Toward Lithium Ionic Liquid Electrolytes - Kalapsazova, Mariya; Kostov, Krassimir; Zhecheva, Ekaterina; Stoyanova, Radostina (Frontiers in Chemistry, 2020)
Hybrid metal ion batteries are perceived as competitive alternatives to lithium ion batteries since they provide better balance between energy/power density, battery cost and environmental requirements. However, their cycling stability and high-temperature storage performance are still far from the desired. Herein, we firstly examine the temperature-induced reactivity of three-layered oxide, P3-Na2/3Ni1/3Mg1/6Mn1/2O2, towards lithium ionic liquid (IL) electrolyte upon cycling in hybrid Li/Na ion cells. Through ex-situ XRD and XPS analyses, the structural and surface changes in P3-Na2/3Ni1/3Mg1/6Mn1/2O2 are monitored and discussed. Understanding the relevant changes occurring during dual Li+ and Na+ intercalation into P3-Na2/3Ni1/3Mg1/6Mn1/2O2 is of crucial importance to enhance the overall performance of hybrid Li/Na ion batteries at elevated temperatures.